A Multidimensional Assessment of Poverty: The Roles of Tourism-Driven GDP Expansion, Hospitality Infrastructure Growth, Tourism Labor Absorption, Human Capital Accumulation, and Core Infrastructure Provision - Gai, Ardiyanto Maksimilianus; Poerwati, Titik; Witjaksono, Agung; Soewarni, Ida (Borong Newinera Publisher, 2026)
Labuan Bajo in West Manggarai has experienced rapid transformation as one of Indonesia’s Super Priority Tourism Destinations. Despite expanding tourism activities, poverty reduction has not occurred proportionally among local communities, raising concerns about the relationship between tourism growth and structural socioeconomic factors. This study examines whether tourism-driven GDP expansion, hospitality infrastructure growth, tourism labor absorption, educational attainment, and core infrastructure provision significantly influence poverty reduction. Using a quantitative correlational design, the research analyzes secondary time-series data from 2010 to 2024. Poverty rate serves as the dependent variable, while independent variables include tourism GDP, number of hotels, tourism employment, average years of schooling, and road infrastructure quality. Data were tested through classical assumption diagnostics and multiple linear regression. Results show that tourism GDP, tourism employment, and road infrastructure quality have significant negative effects on poverty, indicating that income generation, job absorption, and connectivity reduce poverty levels. However, hotel growth and schooling years are not statistically significant. The model demonstrates strong explanatory power, emphasizing the importance of inclusive labor participation and infrastructure access in tourism-led development.